2007
DOI: 10.1177/0021955x07076532
|View full text |Cite
|
Sign up to set email alerts
|

Foaming of Polystyrene/ Thermoplastic Starch Blends

Abstract: This study investigates the fabrication of extruded foams from polystyrene/thermoplastic starch (PS/TPS) blends. A specially designed twinscrew extrusion process is used for starch gelatinization, PS incorporation, polymer mixing, and blowing agent incorporation. In-line rheometry is used to monitor the viscosity of the TPS/PS blends and to evaluate the plasticizing effect of 1,1,1,2 tetrafluoroethane (HFC-134a) used as blowing agent. Differential scanning calorimetry, scanning electron microscopy, density mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2011
2011
2013
2013

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 29 publications
1
25
0
Order By: Relevance
“…In PS and PLA, the TPS particle dimensions were slightly smaller and the particles exhibited more irregular shapes as if they were still in the process of being deformed under flow. The blend morphologies were similar to those reported earlier for PS/TPS and PLA/TPS blends produced using a starch‐slurry incorporation method and the addition of the polymer matrices in the melt state 16, 42. Again, no significant morphological differences were observed when comparing the two compounding processes.…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…In PS and PLA, the TPS particle dimensions were slightly smaller and the particles exhibited more irregular shapes as if they were still in the process of being deformed under flow. The blend morphologies were similar to those reported earlier for PS/TPS and PLA/TPS blends produced using a starch‐slurry incorporation method and the addition of the polymer matrices in the melt state 16, 42. Again, no significant morphological differences were observed when comparing the two compounding processes.…”
Section: Resultssupporting
confidence: 86%
“…Since TPS rheology is very sensitive to plasticization, the blend viscosity ratio can be adjusted by changing the TPS plasticizer level. For glycerol plasticized TPS, for example, the dispersion in PLA, PS, and PE were shown to be particularly coarse until a minimal level of 30 wt% glycerol in the TPS phase was reached 27–29. Finer morphologies were found past this plasticizer concentration threshold with only a slight dependency on further increase plasticizer addition.…”
Section: Introductionmentioning
confidence: 97%
“…Mihai et al [15] investigated the fabrication of ex truded foams from TPS/PS blends using glycerol as plasticizer. It was found that the viscosity of the TPS decreases with increase of the glycerol plasticizer con tent, thus increasing the viscosity ratio between the PS and TPS phase.…”
Section: Tps/ps Blendsmentioning
confidence: 99%
“…This kind of starch composites is called thermo plastic starch (TPS). Several plasticizers have been used for plasticization process to convert starch into TPS to be used in polymer blends such as glycerol [12][13][14][15][16][17][18][19][20][21], water [21,22], urea [23][24][25], formamide [22,[24][25][26], ethylenebisformamide [27][28][29], sorbitol [27,30], citric acid [31], N (2 hydroxyethyl)forma mide [32] and amino acids [20,33]. Water is more ef fective as a plasticizer than glycerol, but the most used plasticizer in TPS preparation is glycerol due to its high boiling point, availability, and low cost.…”
Section: Introductionmentioning
confidence: 99%
“…Although several works can be found for different polymer/fiber combinations, very few studies were devoted to polystyrene foams reinforced with natural fibers. Only, Doroudiani and Kortschot,23 as well as Rizvi et al24 used wood fibers, while Mihai et al25 used starch.…”
Section: Introductionmentioning
confidence: 99%